The Future of Service Post-COVID-19 Pandemic, Volume 1 Rapid Adoption of Digital Service Technology - Lee, Jungwoo; Han, Spring H. (The ICT and Evolution of Work, 2021)
This open access book is geared towards providing insights and stimulating new thinking about the changing nature of services, service work and workers, and service experiences during and after the COVID-19 pandemic in 2020, particularly focusing on digital service technology. This book serves as a useful resource for business practitioners and academics in the areas of service and human resource management. Each chapter deals with specific current issues within these industries due to COVID-19 and issues that will come up post-pandemic. As COVID-19 is expected introduce novel methods to the service sector, such as untact service, telecommuting, alternative work arrangements, job crafting, and new work skills, digital technology is becoming more important than ever before. This books provides a range of examples and cases to elaborate on the effective application of digital service technology in order for businesses to stay relevant in the current climate.